A Survey on English Language Teaching in Nagoya Elementary Schools, Japan - Mustakim, Siti Salina; Mustapha, Ramlee; Lebar, Othman (ATIKAN, 2014)
ABSTRACT: In Japan, the Ministry of Education, Culture, Sports, Science, and Technology has announced the teaching of EFL (English as a Foreign Language) as a compulsory subject for lower age in 2008. To investigate the flexibility for schools and teachers to design their own curriculum in the teaching of EFL in Japan, this study aimed at identifying: (1) the provision of support, resources, training, and time allocation; and (2) the instructional practices employed to the Elementary Schools students in Nagoya, Japan. Instruments in this study are semi-structured interview, classroom observations, and document analysis. Findings were based on cross-sectional survey targeted at exploring the effectiveness of EFL towards teachers, second and fifth graders of students in the Elementary Schools. Results indicated that the resources provided needs improvement on the book utilised to teach. The provision of training is inadequate and requires enhancement. The time allocated needs to be revised from one contact hour in a week to a maximum of two or three contact hours. The instructional practices employed in the classroom were discussed under several categories of systematic instructional practices, diplomatic teaching, the audio-lingual method, and the communicative method of social and information type in the teaching of EFL.KEY WORD: English as a foreign language, Nagoya Elementary Schools, support, resources, training, time allocation, and instructional practices.IKHTISAR: âSatu Tinjauan Mengenai Pengajaran Bahasa Inggeris di Sekolah-sekolah Rendah di Nagoya, Jepunâ. Di Jepun, Kementerian Pendidikan, Kebudayaan, Sukan, Sains, dan Teknologi telah mengumumkan pengajaran BIBA (Bahasa Inggeris sebagai Bahasa Asing) sebagai mata pelajaran wajib untuk umur yang lebih rendah pada tahun 2008. Bagi menyiasat fleksibiliti sekolah dan guru-guru supaya merekabentuk kurikulum sendiri dalam pengajaran BIBA di Jepun, kajian ini bertujuan untuk mengenal pasti: (1) peruntukan sokongan, sumber, latihan, dan agihan masa; serta (2) amalan pengajaran yang digunakan oleh murid-murid Sekolah Rendah di Nagoya, Jepun. Instrumen dalam kajian ini ialah temubual separa berstruktur, pemerhatian bilik darjah, dan analisis dokumen. Dapatan kajian yang berasaskan tinjauan keratan rentas disasarkan untuk meneroka keberkesanan BIBA terhadap guru, murid darjah dua dan darjah lima di Sekolah Rendah. Keputusan kajian menunjukkan bahawa sumber-sumber sedia ada perlu dipertingkatkan pada buku yang digunakan untuk mengajar. Penyediaan latihan tidaklah mencukupi dan memerlukan penambahbaikan. Peruntukkan waktu perlu disemak semula daripada satu jam pertemuan dalam seminggu kepada maksimum dua atau tiga jam pertemuan. Amalan-amalan pengajaran yang digunakan didalam bilik darjah telah dibincangkan di bawah beberapa kategori amalan pengajaran yang sistematik, pengajaran diplomatik, kaedah audio-lingual, serta kaedah komunikatif jenis sosial dan maklumat dalam pengajaran BIBA.KATA KUNCI: Bahasa Inggeris sebagai bahasa asing, Sekolah Rendah Nagoya, sokongan, sumber, latihan, peruntukan masa, dan amalan pengajaran.Â Â Â Â About the Authors: Siti Salina Mustakim is a Ph.D. Scholar and Lecturer at the Faculty of Education and Human Development UPSI (Sultan Idris University of Education), 35900 Tanjung Malim, Perak, Malaysia; Prof. Dr. Ramlee Mustapha is President of Postgraduate Students Association at UPSI in Tanjong Malim, Malaysia; and Prof. Dr. Othman Lebar is Lecturer at the Faculty of Education and Human Development UPSI in Tanjong Malim, Malaysia. Corresponding author is: salinamustakim@gmail.comHow to cite this article? Salina Mustakim, Siti, Ramlee Mustapha & Othman Lebar. (2014). âA Survey on English Language Teaching in Nagoya Elementary Schools, Japanâ in ATIKAN: Jurnal Kajian Pendidikan, Vol.4(2) December, pp.239-254. Bandung, Indonesia: Minda Masagi Press, FKIP UNSUR Cianjur, and FPOK UPI Bandung, ISSN 2088-1290.Â Chronicle of the article: Accepted (September 29, 2014); Revised (October 29, 2014); and Published (December 27, 2014).